Maternal diabetes and hypertensive disorders in association with autism spectrum disorder. Issue 6 (10th April 2019) - Cordero, Christina; Windham, Gayle C.; Schieve, Laura A.; Fallin, Margaret Daniele; Croen, Lisa A.; Siega‐Riz, Anna Maria; Engel, Stephanie M.; Herring, Amy H.; Stuebe, Alison M.; Vladutiu, Catherine J.; Daniels, Julie L.
Abstract : Previous studies have shown complications of pregnancy, often examined in aggregate, to be associated with autism spectrum disorder (ASD). Results for specific complications, such as maternal diabetes and hypertension, have not been uniformly consistent and should be investigated independently in relation to ASD in a large community‐based sample. The Study to Explore Early Development (SEED), a US multisite case–control study, enrolled children born in 2003–2006 at 2–5 years of age. Children were classified into three groups based on confirmation of ASD ( n  = 698), non‐ASD developmental delay (DD; n  = 887), or controls drawn from the general population (POP; n  = 979). Diagnoses of any diabetes or hypertensive disorder during pregnancy were identified from prenatal medical records and maternal self‐report. Logistic regression models estimated adjusted odds ratios (aOR) and confidence intervals (CI) adjusting for maternal age, race/ethnicity, education, smoking during pregnancy, and study site. Models for hypertension were additionally adjusted for parity and plurality. Among 2, 564 mothers, we identified 246 (9.6%) with any diabetes and 386 (15.1%) with any hypertension in pregnancy. After adjustment for covariates, any diabetes during pregnancy was not associated with ASD (aOR = 1.10 [95% CI 0.77, 1.56]), but any hypertension was associated with ASD (aOR = 1.69 [95% CI 1.26, 2.26]). Results were similar for DD, and any diabetes (aOR = 1.29 [95% CI 0.94, 1.78]) or any hypertension (aOR = 1.71 [95% CI 1.30, 2.25]). Some pregnancy complications, such as hypertension, may play a role in autism etiology and can possibly serve as a prompt for more vigilant ASD screening efforts. Autism Res 2019, 12: 967–975 . © 2019 International Society for Autism Research, Wiley Periodicals, Inc. Lay Summary: We studied if common complications in pregnancy are associated with autism spectrum disorder (ASD) in a large sample of mothers and children. Our results show an association between conditions marked by high blood pressure and ASD, but no association with conditions marked by high blood sugar and ASD. Associations were similar for children who had a developmental disorder that was not ASD, suggesting that this relationship may not be specific to ASD.